2013
DOI: 10.1080/19440049.2012.751629
|View full text |Cite
|
Sign up to set email alerts
|

Modelling thermal degradation of zearalenone in maize bread during baking

Abstract: The thermal degradation of zearalenone (ZEA) was investigated using a crust-like model, representing maize bread, which was prepared with naturally contaminated maize flour. Model samples were heated under isothermal conditions at the temperature range of 100-250°C. No reduction was observed at 100°C. Thermal degradation rate constants (k) were calculated as 0.0017, 0.0143 and 0.0216 min(-1) for 150, 200 and 250°C, respectively. Maize bread baked at 250°C for 70 min was used to test the capability of model kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…40 % loss in bread and 20 % in biscuits (Alldrick and Hajšelová 2004 ). Numanoglu et al ( 2013 ) constructed a kinetic model of ZEN degradation in maize bread during baking.…”
Section: Commoditiesmentioning
confidence: 99%
“…40 % loss in bread and 20 % in biscuits (Alldrick and Hajšelová 2004 ). Numanoglu et al ( 2013 ) constructed a kinetic model of ZEN degradation in maize bread during baking.…”
Section: Commoditiesmentioning
confidence: 99%
“…Different from the crumb, higher temperature (≥120 °C) can be achieved in the crust of breads (Numanoglu et al., ; Numanoglu, Yener, Gökmen, Uygun, & Koksel, ; Vidal et al., , ), where an elevated DON loss compared to the inner bread part could be detected (Valle‐Algarra et al., ; Numanoglu et al., ; Giménez et al., ; Wu & Wang, ). Wu and Wang () found the DON loss in the crust to be accompanied by formation of norDONs (norDON A, B, C, and F).…”
Section: Effects Of Food Processing On Mycotoxin Levels In Wheat and mentioning
confidence: 99%
“…During baking, ZON rather tended to increase with longer baking times, but changes were not significant (Cano‐Sancho et al., ). Also, in the production of maize bread, the baking step (250 °C for 70 min) caused no ZON loss in the crumb or only slightly increased the ZON level (by approximately 3% compared to the flour), whereas in the crust, a ZON reduction by 13% was found (Numanoglu et al., ).…”
Section: Effects Of Food Processing On Mycotoxin Levels In Wheat and mentioning
confidence: 99%
“…It is likely that these higher concentrations reported in German flour are due to the fact that they come from unroasted cereal. The gofio is a type of flour that comes from cereal that is toasted at high temperatures (above 200°C), as it has been shown that there is a certain degree of thermal degradation of ZEA above 200ºC (Numanoglu et al, 2013).…”
Section: Occurrence Of Mycotoxins In Gofiomentioning
confidence: 99%